Radical and Marxist theories of crime - Stretesky, Paul B.; Lynch, Michael J. (The library of essays in theoretical criminology, 2016)
pt. I. Definitions and background -- pt. II. Varieties of radical/Marxist criminology -- pt. III. Explaining crime -- pt. IV. Social control : policing and punishment.